The experience of traumatic events disrupts the measurement invariance of a posttraumatic stress scale - Lommen, Miriam J. J.; van de Schoot, Rens; Engelhard, Iris M. (Frontiers in Psychology, 2014)
Studies that include multiple assessments of a particular instrument within the same population are based on the presumption that this instrument measures the same construct over time. But what if the meaning of the construct changes over time due to one's experiences? For example, the experience of a traumatic event can influence one's view of the world, others, and self, and may disrupt the stability of a questionnaire measuring posttraumatic stress symptoms (i.e., it may affect the interpretation of items). Nevertheless, assessments before and after such a traumatic event are crucial to study longitudinal development of posttraumatic stress symptoms. In this study, we examined measurement invariance of posttraumatic stress symptoms in a sample of Dutch soldiers before and after they went on deployment to Afghanistan (N = 249). Results showed that the underlying measurement model before deployment was different from the measurement model after deployment due to invariant item thresholds. These results were replicated in a sample of soldiers deployed to Iraq (N = 305). Since the lack of measurement invariance was due to instability of the majority of the items, it seems reasonable to conclude that the underlying construct of PSS is unstable over time if war-zone related traumatic events occur in between measurements. From a statistical point of view, the scores over time cannot be compared when there is a lack of measurement invariance. The main message of this paper is that researchers working with posttraumatic stress questionnaires in longitudinal studies should not take measurement invariance for granted, but should use pre- and post-symptom scores as different constructs for each time point in the analysis.